Kajian Efesus 4:29 untuk Membangun Prinsip Etika Komunikasi dalam Menanggapi Ujaran Kebencian - Zega, Yanuar Ada; Belo, Yosia (STT Pelita Dunia, 2025)
This study examines communication ethics based on Ephesians 4:29 in responding to hate speech in the digital age. Three main problems are identified: the increasing polarization between groups, the degradation of ethical communication values among Christians, and the minimal implementation of biblical communication principles in the digital context. Using a qualitative method through comprehensive literature review of the Bible, academic articles, and other relevant sources, this research analyzes the communication principles found in Ephesians 4:29. The analysis reveals three fundamental principles: avoiding corrupt speech, speaking words that build up, and prioritizing peace for the hearers. These principles carry theological implications that can be applied as ethical guidelines for Christian communities in responding to hate speech on social media, particularly in the contexts of churches, schools, and families. This research provides a significant contribution to the development of a constructive digital communication paradigm grounded in Christian values.